An investigation of drivers for the need of flexibility in Indian manufacturing industries. (19th July 2019) - Kaur, Shakun Preet; Kumar, Jatinder; Kumar, Rakesh
Presently, the manufacturers all over the world are facing dynamic market conditions. In this scenario, the manufacturing system has to be flexible enough to respond to the conditions of uncertainty. To be future ready and handle these uncertainties the system should identify the key drivers for the need of flexibility and act accordingly. The aim of this paper is to investigate the drivers for the need of flexibility through a survey in Indian manufacturing organisations, the results of the survey are validated through an analytical hierarchy process (AHP) study.